Efficient Hydrogen Evolution Reaction Catalysis in Alkaline Media by All‐in‐One MoS2 with Multifunctional Active Sites. Issue 20 (30th March 2018) - Anjum, Mohsin Ali Raza; Jeong, Hu Young; Lee, Min Hee; Shin, Hyeon Suk; Lee, Jae Sung
Abstract: MoS2 becomes an efficient and durable nonprecious‐metal electrocatalyst for the hydrogen evolution reaction (HER) when it contains multifunctional active sites for water splitting derived from 1T‐phase, defects, S vacancies, exposed Mo edges with expanded interlayer spacings. In contrast to previously reported MoS2 ‐based catalysts targeting only a single or few of these characteristics, the all‐in‐one MoS2 catalyst prepared herein features all of the above active site types. During synthesis, the intercalation of in situ generated NH3 molecules into MoS2 sheets affords ammoniated MoS2 (A‐MoS2 ) that predominantly comprises 1T‐MoS2 and exhibits an expanded interlayer spacing. The subsequent reduction of A‐MoS2 results in the removal of intercalated NH3 and H2 S to form an all‐in‐one MoS2 with multifunctional active sites mentioned above (R‐MoS2 ) that exhibits electrocatalytic HER performance in alkaline media superior to those of all previously reported MoS2 ‐based electrocatalysts. In particular, a hybrid MoS2 /nickel foam catalyst outperforms commercial Pt/C in the practically meaningful high‐current region (>25 mA cm −2 ), demonstrating that R‐MoS2 ‐based materials can potentially replace Pt catalysts in practical alkaline HER systems. Abstract : Defect‐rich, Mo‐edge‐exposed, S‐deficient, and interlayer‐expanded metallic 1T‐MoS2 (R‐MoS2 ) electrocatalysts are successfully synthesized using a unique melamine‐phosphomolybdate (MA‐PMo12 ) supermolecular structure as a precursor. The multifunctional active sites enhance the hydrogen evolution reaction activity of R‐MoS2 .